Estudio de prefactibilidad para la instalación de una planta de fideos a base de harina de yuca - Palomino Ortiz, Adrián Alfredo (2019)
The aim of this investigation concerns the study of the manufacturing process of healthy and nutritional noodles based on cassava flour in order to determinate the commercial, technical, economic and social viability of a Lima-based plant, using tools and technics acquired during the undergraduate period of Industrial Engineering program. The target market is made up of B - C segments of Lima Metropolitan area, composed by people of both sexes between 18 years to more, who want to add to their lives a balanced diet. According to the study, in 2024 it is planned to sell about 23,256 packages of noodles to convenience stores and supermarkets at price of S/ 17.50/ package. The product will be sold in boxes of 12 packages each one (and in turn, each package will contain 12 units of 1kg of noodles). The plant will be located in Lurin district, department of Lima, and will have an area of 525 m2 with a capacity of 279,135 kg/ year. Regarding workforce, it’s scheduled to have only a 01 daily shift with a total of 10 workers keeping the same quantity during the project life (05 years). Administrative workers group will be made up of a total of 08 executives selected carefully in order to satisfy the business core exigencies. The total project investment amounts to S/ 2’486,514 financed by 30% of own-capital and the balance (70%) by Banco Financiero del Peru to an interest rate of 16.3% in increasing quotas without partial grace. According to expected figures, the project provides an economic NPV of S/ 1’642,674 with an economic IRR of 39.71% and a financial NPV of S/ 1’758,071 with a financial IRR of 72.4%. These results indicate that the project will be viable and profitable in both scenarios.